The Influence of Transformational Leadership on Task Performance Through Organizational Commitment - Yuntina, Lily; Sari, Eliana; Karnati, Neti (Green Publisher, 2024)
Performance is the value of a set of behaviors that contribute negatively or positively to the achievement of organizational goals. In the Higher Education unit, efforts to improve Lecturer Task Performance require a leader who has competence and quality and professionalism who can manage all operational activities in an effort to achieve organizational goals. Transformational leadership can be a leadership approach model at this time, meaning that leadership can turn the potential of the institution into energy to improve the quality of Higher Education institutions and their environment. In addition, the variable organizational commitment is also a factor that influences organizational performance. This study aims to determine the Influence of Transformational Leadership and organizational commitment on the Task performance of the Lecturers at the University Muhammadiyah Jakarta. The research used the quantitative approach with the survey. Technically analyzed data is the influence of exogenous variables on the endogenous variables, the path analysis was used. As for respondents, samples of 250 lecturers were taken. The result of the research indicated that: 1) Transformational Leadership had a positive direct influence on Task performance; 2) Organizational Commitment had a positive direct influence on Task performance; and 3) Transformational Leadership had a positive direct influence on Organizational commitment. Thus, improving task performance can be done with good Transformational Leadership and organizational commitment